Odpowiedź :
Zadanie łot tego typu najlepiej rozwiązać sprawdzając każdą z opcji:
A.
-1 * -1 * - 1 + -1 * -1 + -1 = -1 + 1 - 1 = -1
B.
-3(-1 * -1 * -1) + 2(-1 * -1) -(-1) = 3 + 2 + 1 = 6
C.
-(-1 * -1 * -1) - (-1 * -1) -(-1) = 1 - 1 + 1 = 1
D.
2(-1 * -1 * -1) + 3(-1 * -1) +(-1) = -2 + 3 - 1 = 0
Odp: D
Odpowiedź:
x = -1
A.
x³ + x² + x = -1 + 1 - 1 = -1
B.
-x³ - x² - x = 1 - 1 - 1 = 1
C.
-3x³ + 2x² - x = 3 + 2 + 1 = 6
D.
2x³ + 3x² + x = -2 + 3 - 1 = 0
WArtosc 0 przyjmuje wyrazenie D.
Szczegółowe wyjaśnienie: